Diachronic Variation in the Omani Arabic Vernacular of the Al-ʿAwābī District From Carl Reinhardt (1894) to the Present Day - Morano, Roberta (Semitic Languages and Cultures, 2022)
In this monograph, Roberta Morano re-examines one of the foundational works of the Omani Arabic dialectology field, Carl Reinhardt's Ein arabischer Dialekt gesprochen in 'Oman und Zanzibar (1894). This German-authored work was prolific in shaping our knowledge of Omani Arabic during the twentieth century, until the 1980s when more recent linguistic studies on the Arabic varieties spoken in Oman began to appear. Motivated by an urgent need to expand and reinforce our understanding of Omani Arabic, the book provides a linguistic analysis of the Omani vernacular spoken in the al-ʿAwābī district (northern Oman), based on the speech of fifteen informants recruited throughout the area. It also provides a comparative analysis of the new data with that collected by Carl Reinhardt in 1894. This comparison enables the reader to appreciate the extent of diachronic linguistic variation in the region, and also sheds light on the threats that such variation poses to Omani-specific linguistic features. Organised in four chapters, the book presents a sociolinguistic analysis of the Omani linguistic landscape followed by an examination of the phonology, morphology, and syntax of the al-ʿAwābī vernacular. Each chapter contains primary data collected by the author in situ compared, when applicable, with Carl Reinhardt's materials. The appendix includes two sample texts extrapolated from the recordings, fourteen proverbs and one traditional song. This study will be of interest to those working in the fields of Omani Arabic, historical and comparative linguistics, translation and interpretation, or those with an interest in how languages develop over time.